A new design of automatic hanging system / Mohd fIkri Abd Halim - Abd Halim, Mohd fIkri (2009)
Automatic hanging system is one of the project that made special for facilitate the user especially to dry the clothes. The idea for this project comes when the both, husband and wife are too busy with work until does not have time to do work at home, for example to dry the clothes after the clothes are washed. In that case, with this project the user just need to drape all the clothes to where it suppose to be and the sensor will made the system move forward and reverse when it sense the changing weather without human observation. The use is more effective for the dweller in terrace and bungalow and it is very pinch time and energy. The CAD drawing for this project is done by using CATIA V5R17 as well as the structural analysis. The CAD drawing is developed by using the built in part and assembly design inside the CATIA. The structural analysis is using the finite element method available in the CATIA. The structural analysis of the product strength is concentrated on the analysis of the critical parts of the structure. This project also combines with electrical field which is needed in order to operate the automatic system